2013
DOI: 10.1080/00480169.2013.780280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tramadol or morphine in dogs undergoing castration on intra-operative electroencephalogram responses and post-operative pain

Abstract: Tramadol and morphine administered pre-operatively provided a similar degree of post-operative analgesia in male dogs at the doses tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…In a study conducted on dogs, Ptot decreased significantly after electric stimulation followed by administration of morphine (Kongara et al 2010). On the contrary, Ptot did not decrease from baseline in response to castration after administration of morphine (Kongara et al 2013); whereas, tramadol was unable to prevent decrease in Ptot at the time of testicle removal in the same study. This discrepancy in the results reported and results of this study may likely be due to the difference in the experimental conditions or intensity of noxious stimulations used.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In a study conducted on dogs, Ptot decreased significantly after electric stimulation followed by administration of morphine (Kongara et al 2010). On the contrary, Ptot did not decrease from baseline in response to castration after administration of morphine (Kongara et al 2013); whereas, tramadol was unable to prevent decrease in Ptot at the time of testicle removal in the same study. This discrepancy in the results reported and results of this study may likely be due to the difference in the experimental conditions or intensity of noxious stimulations used.…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, changes in EEG variables of nociception in anaesthetised animals and pain in conscious animals have received much attention (Kongara et al 2010, Kongara et al 2014, Zulkifli et al 2014. Most commonly reported EEG variables in animals are median frequency, spectral edge frequency 95% and total power (Haga and Dolvik 2005, Gibson et al 2007, Murrell et al 2007, Kongara et al 2013). Median frequency is "the frequency below which 50% of the total power of the EEG is located".…”
Section: Introductionmentioning
confidence: 99%
“…However, this use in dogs is controversial, since clinical efficacy studies have produced conflicting results. Some studies indicate that tramadol is equally or more effective than other drugs used to treat pain in dogs (Mastrocinque and Fantoni, 2003;Almeida et al, 2010;Martins et al, 2010;Clark et al, 2011;KuKanich and Papich, 2011;Malek et al, 2012;Neves et al, 2012;Rialland et al, 2012;Kongara et al, 2013;Morgaz et al, 2013;Teixeira et al, 2013;Cardozo et al, 2014), whereas other studies have shown relatively poor analgesic efficacy in dogs (Davila et al, 2013;Delgado et al, 2014;Kögel et al, 2014). Tramadol is considered a prodrug with regard to opioid analgesic effects, requiring metabolic activation by cytochrome P450 (P450) enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…other minimal anaesthesia studies(Murrell et al 2010;Kongara et al 2013). These results reflect 335 the difficulty of maintaining normocapnia in cattle and are not unusually high for large ruminants 336(Klein & Fisher 1988).…”
mentioning
confidence: 99%